WOUND CARE WITH MOIST WOUND DRESSINGS FOR HEALING DIABETIC GANGRENE: SYSTEMATIC REVIEW - Wuryani, Ary Dwi (Lux Mensana: Journal of Scientific Health, 2023)
Introduction. Wound care with moist wound dressings is an effective and beneficial option for treating diabetic ulcers which often result in healing of old wounds that end in amputation. Writing this literature review aims to identify the effectiveness of the use of wound care with diabetic gangrene moist wound dressing.  Method. The literature review writing method goes through several stages: creating questions and keywords namely MESH (Medical Subject Heading), identification, eligibility, selection of article inclusions, screening, and assessment. The selection process listed in the literature framework resulted in 4 articles. Articles are summarized and assessed using critical appraisal according to the research design in each article. Result&Analysis. The wound care method with moist wound dressings has been proven to significantly help the healing process of diabetic gangrene wounds. The wound care method with the principle of moisture balance, is more effective than conventional methods. Discussion. Modern dressing wound care has been proven to help heal diabetic wounds effectively, this is evidenced by the mechanism of the average decrease in the occurrence of the wound dressing process and an increase in the quality of life of diabetic ulcer wound patients after being treated with modern wound dressing methods.